Sorption kinetics and equilibrium isotherms of phosphine and evaluation of chlorine dioxide gas during wheat fumigation - Buenavista, Rania Marie (Kansas State University, 2022)
Increased genetic-based resistance to widely used fumigant phosphine among stored-product insect species is a result of fumigating challenges in leaky pest management practices. Phosphine can be prolonged for use as a fumigant through proper fumigation practices and efficient insect resistance monitoring. Along with prolonging the use of phosphine, it is also critical to find potential fumigant alternatives that could effectively control stored-product insects once phosphine is no longer effective. In the first study, fumigation flasks, half-filled with hard red winter wheat, were fumigated to achieve desired phosphine concentration levels of 400, 700, 1000, 1500, 2000, and 2400 ppm at 25°C. Gas chromatographic analysis of headspace gas showed the change in concentration through time until it reached an equilibrium. Pseudo-first order and pseudo-second order kinetic models were fitted to phosphine sorption data and sorption isotherms were plotted fitting Langmuir, Freundlich, and Redlich-Peterson sorption isotherm models. All three models showed good fit (standard error of prediction = 0.46-0.47). Higher equilibrium concentration was observed at the maximum phosphine concentration (2400 ppm), indicating that maximum adsorption capacity of wheat kernels was still not met. Total sorbed phosphine at equilibrium was important in determining the rate and maximum quantity of phosphine uptake in wheat. The second objective of this study focused on further evaluation of chlorine dioxide as a potential fumigant in terms of wheat kernel and flour characteristics. Hard red spring wheat kernels were exposed to varying levels of gaseous ClO₂ concentrations (200, 300, 400, and 500 ppm) and held in a gas-tight bucket assembly for 24 h after achieving the nominal concentration. Three vials containing 20 unsexed adults of lesser grain borer (Rhyzopertha dominica (Fabricius)) were placed at top, middle, and bottom layers of wheat mass during fumigation to assess insect mortality. ClO₂ gas treatment achieved complete insect mortality at 500 ppm across all vial locations. Adult progeny reduction was found to be highest for 500 ppm treatment ranging from 96 to 99%. Significant reduction (37.7-51.1%) in germination rate resulted after exposure to 300-500 ppm. In terms of flour color, lightness value significantly increased after treatment of 200-500 ppm. The pH value of wheat flour had significant reduction from 6.2 to 6.1 after 500 ppm treatment. In terms of pasting characteristics, peak and final viscosities of ClO₂-treated wheat flour at 200-500 ppm significantly decreased from 3303.7 to 3073.3 cP and from 3515.0 to 3208.3 cP, respectively. No significant difference was observed in flour quality and functionality parameters, including falling number, trough viscosity, breakdown viscosity, starch damage, and mixolab dough behavior properties. Overall, ClO₂ gas treatment at 500 ppm was effective in killing adult lesser grain borers without negatively affecting wheat flour quality parameters but affected wheat kernel viability.
Keywords: Sorption; Phosphine; Chlorine dioxide; Wheat; Flour quality